Management of Helicobacter pylori Infection in Europe: Focusing on the Maastricht V/Florence Consensus - Woon Geon Shin (Yong Chan Lee, 2017)
In the fifth edition of the Maastricht Consensus Conference, quadruple regimens for primary treatment of Helicobacter pylori infection such as concomitant or bismuth quadruple therapy have been recommended in areas of high clarithromycin resistance. In addition, the Maastricht Consensus V highlighted the importance of population- and individual-based susceptibility tests to detect possible antibiotic resistance in patients with a history of intake of any of the key antibiotics, even if the population has a low resistance rate.